Metarhizium anisopliae dan Andrographis paniculata Terhadap Serangga Bukan Hama Sasaran - Dini Yuliani (Institut Pertanian Bogor, 2016)
The objective of this study was to determine the effect of Metarhizium anisopliae and Andrographis paniculata to the natural enemies of Nephotettix virescens and non-target insect pests. This research was conducted in tungro endemic areas in Subang District, West Java in the wet season 2013/2014. The method of research used a split plot design with four replications. The main plot was IR66, Inpari 9, and Ciherang varieties. Subplot was the application of M. anisopliae, A. paniculata, and control. Observations were carried out five times started at nursery (2 weeks after seedling), 14, 28, 42, and 56 days after planting using insect nets, double swing 10 times on each plot observations. The results show M. anisopliae and A. paniculata not adversely affect on non-target insect pests such as Chironomid and natural enemies of N. virescens namely Lycosa pseudoannulata, Cyrtorhinus lividipennis, Sepedon sp., damselfly, Tipulidae sp., Telenomus sp., dragonfly, and Tetrastichus sp.. Efficacy of M. anisopliae and A. paniculata as one of the control strategies that are environmentally friendly and proved not harmful to non-target insect pests.